THE CHARACTERISATION AND POLLUTANT LOAD OF GREYWATER CONTAINING PERSONAL CARE COSMETIC PRODUCTS (PCCPS) FOR BODY CARE - Marisa Handajani; Indira Nathania Pamio; Mindriany Syafila; Nur Novilina Arifianingsih (Universitas Trisakti, 2023)
Personal Care Cosmetic Products (PCCPs) are used on the exterior of the body, such as the skin, nails, hair, lips, external genitalia, teeth, and oral membranes. Greywater from a bathing activity is a significant contributor to domestic wastewater quantity. The greywater contains residual substances from the rinsing process of body care products. Aim: This study will focus on the characteristic and the specific pollutant load of greywater generated from the usage of shower gel. Methodology and Results: The characterization and specific pollutant loads are conducted based on artificial greywater which is made from three brands of shower gel which is diluted in tap water. The greywater from body cleaning activities has a pH value in the range of 7.26-7.33; total phosphate in the range of 1.71-3.09 mg/L; the value of NTK total Kjedahl nitrogen in the range of 2.45-4.03 mg/L; total COD in the range of 380.97-506.16 mg/L; dissolved COD values in the range of 310.92-393.68 mg/L; TSS value in the range of 62-229.50 mg/L; and TDS values in the range of 283-376.67 mg/L. The specific pollutant load generated from shower gel usage in greywater are 0.012 g TP/person/day; 0.016 g TKN/person/day; 2.14 g Total COD/person/day; 1.59 g dissolved COD/person/day; 0.94 g/person/day for TSS; and 1.48 g/person/day for TDS. Conclusion, significance, and impact study: The Greywater from shower gel usage contains physical and chemical constituents that can promote environmental deterioration. The finding of this research will provide useful information for domestic wastewater management and system design, especially for urban areas in Indonesia.